Lifelong learning and nurses' continuing professional development, a metasynthesis of the literature - Mandlenkosi Mlambo; Charlotte Silén; Cormac McGrath (BMC, 2021)
Abstract Background Continuing professional development (CPD) is central to nurses' lifelong learning and constitutes a vital aspect for keeping nurses' knowledge and skills up-to-date. While we know about the need for nurses' continuing professional development, less is known about how nurses experience and perceive continuing professional development. A metasynthesis of how nurses experience and view continuing professional development may provide a basis for planning future continuing professional development interventions more effectively and take advantage of examples from different contexts. The aim of this paper is to conduct such a metasynthesis, investigating the qualitative research on nurses' experiences of continuing professional development. Methods A metasynthesis of the qualitative literature was conducted. A total of 25 articles fulfilled the inclusion criteria and were reviewed. Results We determined five overarching themes, Organisational culture shapes the conditions, Supportive environment as a prerequisite, Attitudes and motivation reflect nurse's professional values, Nurses' perceptions of barriers and Perceived impact on practice as a core value. This metasynthesis highlights that nurses value continuing professional development and believe that it is fundamental to professionalism and lifelong learning. Moreover CPD is identified as important in improving patient care standards. Conclusions Based on the metasynthesis, we argue that access to continuing professional development could be made more attainable, realistic and relevant. Expediently, organizations should adequately fund and make continuing professional development accessible. In turn, nurses should continue to actively engage in continuing professional development to maintain high standards of nursing care through competent practice. This paper highlights the perceived benefits and challenges of continuing professional development that nurses face and offers advice and understanding in relation to continuing professional development. We believe that this metasynthesis contributes with insights and suggestions that would be valuable for nurses and policy makers and others who are involved in nurse education and continuing professional development.